Method for optimizing the treatment of acute respiratory diseases in children - Нiкiтiна Надiя Олександрiвна; Nikitina N. О.; Беспалова А. В.; Кукушкін Віталій Наумович; Kukushkin, V. N; Bespalova A. V. (Svishtov, Bulgaria : Tsenov Academy of Economics, 2024)
The results of treatment of children with acute respiratory tract diseases using the medicament Bon-appetit during a period of decreased activity of the inflammatory process are presented. The medicament is well tolerated (85%) with minor side effects (14% - bowel disorder, drowsiness, thirst). Normalization of acute phase parameters was observed, and external respiration function was restored faster. The use of the medicament Bon-appetit during the recovery period contributed to the relief of the main symptoms of the disease of the middle and lower respiratory tract due to its anti-inflammatory, expectorant, antioxidant, antitoxic, immunomodulatory and restorative effects.

Наведено результати лікування дітей з гострими захворюваннями дихальних шляхів з використанням препарату Бон-апетит у період зниження активності запального процесу. Переносність препарату хороша (85%) при незначні побічні ефекти (14% - послаблення випорожнень, сонливість, спрага). Спостерігалася нормалізація острофазових показників, швидше відновлювалась функція зовнішнього дихання. Застосування препарату Бон-апетит у період одужання сприяв купірування основних симптомів захворювання середніх та нижніх дихальних шляхів завдяки протизапальному, відхаркувальному, антиоксидантному, антитоксичному, імуномодулюючому та загальнозміцнювальному діям.
Nikitina N. О. Method for optimizing the treatment of acute respiratory diseases in children / N. О. Nikitina, A. V. Bespalova, V. N. Kukushkin // SWorld journal. - Svishtov, Bulgaria : Tsenov Academy of Economics, 2024. - Issue № 24, Part 2. - Р. 88-94. DOI: 10.30888/2663-5712.2024-24-00-042
Keywords: appetite; children; Bon-appetite; bronchitis; pneumonia; апетит, діти, Бон-апетит, бронхіт, пневмонія